Educación Integral para el Éxito Profesional del Administrador (2020)
Education in Mexico has been the subject of study for decades, in media such as international congresses, public policies, plans and government programs that have determined the importance it has in teaching and transcendence for the training of students in basic education articulated with educational programs that lead to integral education, seen as the formation of aspects: intellectual, emotional, social, physical, that strengthen children and thus acquire the skills and values ​​to face a demanding and competitive society as professionals. The research was conducted in 3 primary schools in the city of Puebla, all agreed that students graduate with low academic performance, lack of values ​​and poor skills, so when they arrive at the University where we receive them, they present weaknesses in knowledge, commitment, responsibility. Therefore it is necessary to implement a model of Integral Education with which the necessary knowledge and skills are obtained that in turn would motivate them to enter the University and likewise would graduate with the skills that allow them a better performance as professionals to occupy a place in the MSMEs that represent 90% of the Companies in Puebla and generate 72% of employment (INEGI 2017) being the source of subsistence for the Poblana society